2006
DOI: 10.1089/thy.2006.16.1163
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Markers in the Follow-up of Medullary Thyroid Cancer

Abstract: Medullary thyroid cancer (MTC) shares biochemical features with other neuroendocrine tumors but the particular characteristics are largely unexplored. We investigated the biochemical neuroendocrine profile of MTC and whether specific markers could be useful in follow-up. In addition to the standard tumor marker calcitonin, plasma carcino-embryonic antigen (CEA), plasma catecholamines, (platelet) serotonin, chromogranin A, tryptase, and urinary markers of catecholamine, histamine, and serotonin metabolism were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 40 publications
(44 reference statements)
4
27
0
Order By: Relevance
“…This illustrates the importance of applying scientific knowledge in patient care, which may have significant effects on the outcome of malignant disease. Similar results have been reported in other studies (4,10,19). In an older study, Modigliani et al (5) reported biochemical cure in 37.6% in sporadic cases, which is lower compared with the remission rate in our groups before 2001 (41.5%) and after 2001 (61.2%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This illustrates the importance of applying scientific knowledge in patient care, which may have significant effects on the outcome of malignant disease. Similar results have been reported in other studies (4,10,19). In an older study, Modigliani et al (5) reported biochemical cure in 37.6% in sporadic cases, which is lower compared with the remission rate in our groups before 2001 (41.5%) and after 2001 (61.2%).…”
Section: Discussionsupporting
confidence: 91%
“…The stage of the disease and the tumor extent at presentation are significant predictors of life expectancy, thus early diagnosis is important for the outcome of the disease (4). Furthermore, the postoperative calcitonin (CT) levels as well as the calcitonin and carcinoembryonic antigen (CEA) doubling time have been proposed as predictive factors for the outcome and the progression rate of the disease (5,6,7,8,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…31 As it is in our case; there are some false positivity reasons related to CEA but this is the first report showing a false positivity in the literature as far as we know.…”
supporting
confidence: 52%
“…C cells are derived from the neuronal crest and are part of the amino precursor uptake and decarboxylation system [1][2][3]. C cells secrete a number of compounds, including the polypeptide hormone calcitonin and carcinoembryonic antigen (CEA) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%